A study of self-medication practices among medical students - Rasania, Shreya; Dambhare, Dharampal; Priyanka; Srivastava, Akshit; Rasania, Prasann (International Journal of Research in Medical Sciences, 2023)
Background: Self-medication is widely prevalent in India, more so among medical students as they have easy access to information from drug indices, literature and physician samples. Methods: This was a descriptive cross-sectional type of study conducted among undergraduate students of a medical college in Maharashtra. Minimum sample size came out to be 259 by taking prevalence of self-medication as 78.6% from a previous study conducted on similar population. 75 students each were randomly selected from all four batches of MBBS. Data collection was done by using pretested questionnaire and it was analysed using SPSS version 22. Qualitative data was expressed in proportions and quantitative data was expressed in mean and standard deviation. Chi square test was used to check the association of various factors and self-medication practice. Results: The prevalence of self-medication was found to be 72.1%. The practice was significantly more common in females, those belonging to urban areas and those from senior batches of MBBS (p<0.05). Headache (34.2%), acidity (25.7%) and fever (24.3%) were most common indications and antipyretics (28.2%), antihistamincs (17.3%) and analgesics (11.4%) were commonly used drugs for self-medication. In spite of being aware about the side effects of self-medication and importance of completing antibiotic course, their practices were largely unfavourable. Previous prescriptions (45.5%), family members (23.8%), pharmacist (21.8%) and medical textbooks (18.3%) were sources of information about self-medication. Conclusions: Self-medication was highly prevalent among medical students with more prevalence among females, students from urban areas and senior students. The practices of students were also unfavourable.